The UK's covid-19 data collection has been "world beating"—let's not throw it away. (25th February 2022) - Dowd, Jennifer Beam
Abstract : It is critical the UK keeps the bones of its world leading data infrastructure so that we can protect ourselves from lingering and future threats, writes Jennifer Beam Dowd